Empowering Gucang Farm Catfish MSME Through Digital Training on Marketplace Optimization and Social Media Engagement - Cynthia Anna Wijayanti; Juniarty Siahaan (Pascasarjana Universitas Mataram, 2026)
The community initiative focuses on accelerating the digital transformation of the Gucang Farm catfish MSME through structured training on marketplace utilization and social media engagement. Pre-observations identified several gaps, including limited digital literacy, a minimal online presence, and weak promotional strategies, collectively hindering the competitiveness and revenue potential of local catfish producers in Tigaraksa District. To address these, the program provided a practical training module covering Google My Business registration, Tokopedia and TikTok Shop setup, product photo and video creation, persuasive product description writing, and basic e-commerce management. Participants were guided step-by-step in creating active marketplace accounts, uploading product catalogs, managing customer interactions, and implementing simple analytics to monitor online sales performance. The training also introduced strategies to enhance social media visibility and customer engagement, emphasizing consistency, storytelling, and content quality. Results demonstrated increased confidence and digital readiness among participants, with all groups successfully activating at least one marketplace or WhatsApp Business account. The initiative aligns with the targeted outcomes of improving online access, increasing monthly sales by 20–30%, and strengthening digital capacity among MSME members. Overall, this program actively demonstrates how practical, hands-on digital marketing training enhances MSME competitiveness and drives sustainable economic growth in local aquaculture communities.